2002
DOI: 10.1161/01.cir.0000042673.07632.76
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin and Risk of Myocardial Infarction and All-Cause Mortality in the Framingham Offspring Study

Abstract: Background-Coronary disease remains the leading cause of death in the United States. The association between serum albumin and cardiovascular disease remains controversial. We used data collected prospectively from participants of the Framingham Offspring Study to assess whether a lower concentration of serum albumin was associated with an increased risk of myocardial infarction (MI) and all-cause mortality. Methods and Results-During 21.9 years of mean follow-up, 280 cases of MI occurred. From the highest to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
149
2
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(163 citation statements)
references
References 24 publications
8
149
2
4
Order By: Relevance
“…Abbasi and colleagues found no significant association in one of their cohorts of men and women aged 28-75 years [13]. In the Atherosclerosis Risk in Communities study [8], low serum albumin was associated with an increased risk of type 2 diabetes among men and women aged 45-65 years in analyses [6,11,12], cancer mortality [6] and allcause mortality [11]. Our findings of a positive association are at odds with previous findings.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Abbasi and colleagues found no significant association in one of their cohorts of men and women aged 28-75 years [13]. In the Atherosclerosis Risk in Communities study [8], low serum albumin was associated with an increased risk of type 2 diabetes among men and women aged 45-65 years in analyses [6,11,12], cancer mortality [6] and allcause mortality [11]. Our findings of a positive association are at odds with previous findings.…”
Section: Discussioncontrasting
confidence: 87%
“…We, however, used the BCP assay, which agrees more closely with the gold standard of immunonephelometry [25]. Fourth, there are suggestions that low serum albumin concentrations may be an indicator of underlying subclinical disease (such as renal or liver disease, malnutrition and anaemia) [11,14], which may produce spurious inverse associations with type 2 diabetes and other chronic conditions [26]. The current study differs in several important ways from previous studies, which enhances the reliability of the findings: (1) the analysis was based on a large dataset with adequate power to demonstrate the observed associations; (2) participants were selected from a nationally representative sample, with a high response rate; they were prospectively followed for an average period of 20 years and there was no loss to follow-up; (3) there was information on a comprehensive panel of lifestyle and biological markers to allow adequate adjustment for potential confounding; and (4) individuals with prevalent diabetes, CVD, liver disease or renal disease were excluded from the analyses; in addition, a sensitivity analysis excluded diabetes events in the first 5 years of follow-up, thus minimising the effects of any pre-existing disease on serum albumin concentrations ('reverse causation') and therefore more closely reflecting a causal association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…96 Serum ferritin could be another inflammatory biomarker or a representative of iron overload, which is known to increase post-HCT morbidity and mortality. 97 Low serum albumin is a predictive for cardiovascular complications and mortality in the general and geriatric populations 98,99 and has been used in other prognostic systems, 100 but was never previously assessed as a pre-HCT predictor of outcomes. Low platelet counts might be a sensitive measure of the impacts of prior treatment on marrow function.…”
Section: Could the Hct-ci Be Augmented? Is There Any Additional Role mentioning
confidence: 99%
“…1,2 Recently it has been demonstrated that impaired renal function and increased urinary albumin concentrations, even within normal range, are associated with increased CV morbidity and mortality. [3][4][5][6][7][8] Over the past 10 years, the incidence of diabetic nephropathy has increased by 150% in both the United States (USA) and Europe. 9 Almost 40% of patients starting dialysis in the USA have diabetes, 9 and the incidence of both all-cause and CV death is considerably higher in diabetic than in nondiabetic patients.…”
Section: Introductionmentioning
confidence: 99%